The over-the-counter securities markets - Loll, Leo M.; Buckley, Julian G. (Englewood Cliffs, N.J. : Prentice-Hall, 1973)
The book provides a useful tool in solving the complex invest problems that confront the securities salesman daily.
Includes index
ucj 17/01/2019
Loans
Keywords: Over-the-counter markets